Efficacy and Safety of Tranexamic Acid in Orthopaedic Fracture Surgery: A Meta-Analysis and Systematic Literature Review. Issue 10 (October 2017) - Amer, Kamil M.; Rehman, Saqib; Amer, Kamal; Haydel, Christopher
Abstract : Background: Tranexamic acid (TXA) is an antifibrinolytic drug that has been shown to be effective in reducing blood loss and the need for transfusions after several orthopaedic surgeries. However, the effectiveness of TXA use in orthopaedic fracture surgeries still remains unclear. The purpose of this meta-analysis was to review existing literature with interest in the effectiveness and safety of TXA treatment in reducing total blood loss and transfusion rates for patients who underwent surgery for fracture repairs. Methods: An electronic literature search of PubMed, Embase, OVID, and the Cochrane Library was conducted to identify studies published before December 2016. All randomized controlled trials and cohort studies evaluating the efficacy of TXA during fracture repair surgeries were identified. Primary outcome measures included the number of patients receiving a blood transfusion and perioperative total blood loss. Data were analyzed using Comprehensive Meta-Analysis (CMA) statistical software. Results: Seven studies encompassing 559 patients met the inclusion criteria for the meta-analysis. Our meta-analysis indicated that when compared with the placebo control group, the use of TXA in fracture surgeries significantly reduced total blood loss by approximately 330 mL ( P = 0.009), reduced the transfusion rate with a relative risk of 0.54 ( P < 0.001), and decreased the drop of hemoglobin by 0.76 g/dL ( P < 0.001). There was no significant difference between the number of thromboembolic events among the study groups ( P = 0.24). Conclusions: This study demonstrated that tranexamic acid may be used in orthopaedic fracture surgeries to reduce total blood loss, transfusion rates, and the drop in hemoglobin level, without increasing risk of venous thrombo-embolism. A limitation to these findings is the small number of studies available. Further studies need to be conducted to confirm these findings. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.